2022
DOI: 10.5433/1679-0359.2022v43n3p1355
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance profile of Staphylococcus spp. isolates in cattle herds from Western Amazon

Abstract: Staphylococcus is one of the most frequent etiological agents of bovine mastitis, causing economic losses to milk farming. This study aimed to describe the milk production and management practices in 15 herds located in three microregions of the State of Rondônia and to identify the antimicrobial resistance profile of 97 isolates of the genus Staphylococcus from these herds. The isolates were subjected to antimicrobial susceptibility tests using the agar diffusion method. Twenty-nine S. aureus isolates were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The most prevalent patterns were resistance to penicillin, ampicillin and tetracycline. 51 In another study, it was observed that five of the six Escherichia coli isolates collected from mastitic milk showed multi-resistance to the antimicrobials tetracycline, neomycin and gentamicin. 52 In a survey carried out with 120 strains of E. coli isolated from bovine mastitis, it was shown that 20% of strains of this bacterium were resistant to two or more antimicrobials.…”
Section: Groupmentioning
confidence: 98%
“…The most prevalent patterns were resistance to penicillin, ampicillin and tetracycline. 51 In another study, it was observed that five of the six Escherichia coli isolates collected from mastitic milk showed multi-resistance to the antimicrobials tetracycline, neomycin and gentamicin. 52 In a survey carried out with 120 strains of E. coli isolated from bovine mastitis, it was shown that 20% of strains of this bacterium were resistant to two or more antimicrobials.…”
Section: Groupmentioning
confidence: 98%